Event-driven perception for agent-based simulation : a tileworld example - Singh, Lakhdeep. (2012)
This report contains the details regard the work done by Lakhdeep Singh for his Final Year Project. The project, Event-driven perception for Agent-based simulation: A Tileworld Example, involved redesigning the agent-based model (ABM) as an event-driven model. The end product of this project was to create a library which would make it easy for users to implement event-driven ABM. This library is called Event Driven Agent Simulation (EDAS). The EDAS is built upon the existing MASON framework, and is coded in JAVA.